Agroforestry Technologies for resource conservation and production of degraded lands - Mishra, P. K.; Kaushal, R.; Chaturvedi, O. P. (Indian Farming, 2015)
Productive lands are subjected to various degrees of degradation and are fast turning into wastelands. Increasing population pressure, biotic pressure, unplanned urbanization, break down of traditional institutions for managing Common Property Resources and lack of appropriate management practices are some of the key reasons for land degradation. The land degradation has both on-site and off-site impacts which need to be managed properly. Degraded lands can be suitably reclaimed for agriculture or other alternate uses following afforestation, agroforestry and bio-engineering measures which are simple and cost effective. In last 3-4 decades, CSWCRTI and its research centres have developed many agroforestry based technologies. The adoption of these agroforestry systems by stakeholders has been very encouraging. Silvipasture, agrihorticulture and hortipasture system are being adopted by farmers on degraded lands for enhancing productivity, income and conserving the resources on sustainable basis. Many of the village community lands, government lands, absentee lands, degraded watersheds have been rehabilitated by these agroforestry systems. The work on refinement of these technologies for further upscaling is also in progress.